Method for co-production of bio-based pentanediol and propanediol from dihydropyran and hydroxypropionic acid
Patent Information
- Application Number
- CN202211418761.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-11-14
AI Technical Summary
[0006]本发明的目的在于提供一种以二氢吡喃和羟基丙酸为原料联产生物基戊二醇和丙二醇的方法,具体涉及通过二氢吡喃与3-羟基丙酸为原料经过加成酯化过程得到四氢吡喃羟基丙酸酯,进一步加氢得到目标产物1,5-戊二醇和1,3-丙二醇,该过程克服现有1,5-戊二醇生产过程中原料戊二酸短缺问题,克服1,3-丙二醇生产过程中条件苛刻、原料毒性大及发酵法效率低等问题,该过程具有工艺简单,过程绿色,同时联产两种关键生物基聚酯奇数碳二元醇单体等优势
[0017]本发明与现有技术相比,其有益效果是:本发明的方法实现生物质资源高效利用同时生产两种奇数碳的端位二元醇(1,5-戊二醇和1,3-丙二醇),同时该方法流程简单、绿色环保,全流程不使用贵金属催化剂。
Abstract
Description
Technical Field
[0001] This invention relates to a method for producing bio-based pentanediol and propylene glycol from dihydropyran and hydroxypropionic acid, specifically a method for producing bio-based pentanediol and propylene glycol from dihydropyran and hydroxypropionic acid as raw materials. Background Technology
[0002] 1,5-Pentanediol is an important odd-numbered carbon diol, primarily used in the production of polymeric materials such as polyesters and polyurethanes. It can also be used in the production of UV-curable coatings, plasticizers, fragrances, and inks. 1,3-Propanediol is also an important odd-numbered carbon diol, mainly used in the production of polyesters and polyurethanes. Industrially, 1,5-Pentanediol is produced from glutaric acid via direct hydrogenation or esterification with methanol followed by hydrogenation. The main companies possessing these technologies are BASF of Germany and UBE of Japan. However, glutaric acid is a byproduct of the oxidation of cyclohexane to adipic acid, and its limited availability restricts the production scale of 1,5-Pentanediol.
[0003] The main methods for industrial production of 1,3-propanediol include DuPont's glycerol fermentation method, Evonik's acrolein hydration method, and Shell's ethylene oxide method. Currently, the fermentation method suffers from low efficiency, the acrolein method uses toxic raw materials, and the ethylene oxide method requires stringent high-temperature and high-pressure conditions.
[0004] Lignocellulosic biomass is the only abundant and CO2-neutral carbon-containing renewable resource, and its conversion and utilization align with the concept of sustainable green development. Furfural, currently the most widely used chemical in biomass industrial applications, is driving the development and progress of the biomass industry. The technologies for hydrogenating furfural to tetrahydrofurfuryl alcohol and dehydrating tetrahydrofurfuryl alcohol to dihydropyran are relatively mature and have been successfully applied industrially. Furthermore, the technology for producing 3-hydroxypropionic acid through biomass fermentation is developing rapidly, with extensive research propelling this technology towards industrial application.
[0005] Therefore, this invention proposes a route using biomass raw materials dihydropyran and 3-hydroxypropionic acid as feedstocks to co-produce bio-based 1,5-pentanediol and 1,3-propanediol via addition esterification followed by hydrogenation, simultaneously achieving the production of two key bio-based polyester odd-numbered carbon diol monomers. This method does not use any precious metal catalysts throughout the entire process, and no solvents other than dihydropyran and 3-hydroxypropionic acid are used, making the process green and simple. Summary of the Invention
[0006] The purpose of this invention is to provide a method for co-producing bio-based pentanediol and propylene glycol using dihydropyran and hydroxypropionic acid as raw materials. Specifically, it involves obtaining tetrahydropyran hydroxypropionic acid ester by addition esterification of dihydropyran and 3-hydroxypropionic acid, followed by further hydrogenation to obtain the target products 1,5-pentanediol and 1,3-propanediol. This process overcomes the problem of glutaric acid shortage in the existing 1,5-pentanediol production process, as well as the problems of harsh conditions, high toxicity of raw materials, and low efficiency of fermentation in the 1,3-propanediol production process. This process has the advantages of simple process, green process, and co-production of two key bio-based polyester odd-carbon diol monomers.
[0007] The technical solution adopted in this invention is as follows:
[0008] Using dihydropyran and 3-hydroxypropionic acid as raw materials, in the presence of a solid acid molecular sieve catalyst, dihydropyran and 3-hydroxypropionic acid undergo an addition esterification reaction, followed by separation to obtain tetrahydropyran hydroxypropionate. Then, in the presence of a hydrogenation metal catalyst, using the tetrahydropyran hydroxypropionate product as a raw material, in a hydrogen atmosphere, the tetrahydropyran hydroxypropionate undergoes a hydrogenation reaction to produce the target products 1,5-pentanediol and 1,3-propanediol. In a preferred embodiment, the solid acid catalyst is one or more of ZSM-5 and β molecular sieves.
[0009] In a preferred embodiment, the hydrogenation metal catalyst comprises three parts: a metal active component, an additive, and a support; the metal active component is one or more of the metal elements Cu, Ni, and Co; the mass content of the metal active component accounts for 2-50% of the catalyst weight; the additive is one or more of the additive elements Zn, B, Zr, Ga, and La; the mass content of the additive accounts for 0.01-8% of the catalyst weight; the support is an inorganic porous material selected from one or more combinations of SiO2, Al2O3, TiO2, silicon-aluminum mixed oxide, titanium-silicon mixed oxide, diatomaceous earth, kaolin, and activated carbon.
[0010] In a preferred embodiment, the addition esterification reaction conditions are: 50–200°C, reaction pressure of 0.1–10 MPa, and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 20:1–1:20.
[0011] In a preferred embodiment, the conditions for the hydrogenation reaction are: a reaction temperature of 150–300°C, a reaction pressure of 0.1–15 MPa, and a molar ratio of hydrogen to tetrahydropyran hydroxypropionate of 5:1–100:1.
[0012] In a preferred embodiment, the reactor required for the addition esterification reaction and the hydrogenation reaction is selected from one of the following: fixed bed, slurry bed, fluidized bed, and high-pressure reactor.
[0013] In a preferred embodiment, the hydrogenation catalyst is prepared using at least one of the following methods: impregnation, precipitation, and physical grinding. Specifically: the impregnation method involves adding a certain amount of a metal salt mixture solution to an inorganic porous support, followed by drying and calcination to obtain the catalyst; the precipitation method uses a metal salt mixture solution as a metal precursor and one or more of urea, ammonia, sodium carbonate, and sodium hydroxide as a precipitant, adding the metal precursor to the precipitant solution at a certain temperature, or adding the precipitant solution to the metal precursor, or simultaneously adding the metal precursor and precipitant to a precipitation vessel containing a solvent; after aging, the mixture undergoes filtration, washing, drying, and calcination to obtain the catalyst; the physical grinding method involves directly mechanically mixing the inorganic porous support and the metal salt in a mortar or ball mill, followed by drying and calcination to obtain the catalyst.
[0014] In a preferred embodiment, the drying temperature is 60–150°C, the calcination temperature is 250–800°C, the deposition temperature is 25–90°C, and the aging temperature is 25–90°C.
[0015] In a preferred embodiment, inorganic porous materials may be selectively added to the precipitation process.
[0016] In a preferred embodiment, the hydrogenation catalyst needs to be activated before use. The activation is carried out in a hydrogen-containing atmosphere with a hydrogen content of 0.05-100%, and the activation conditions are: temperature 100-800°C, time 0.5-72 h, and gas space velocity 10-10000 h⁻¹.
[0017] Compared with the prior art, the beneficial effects of this invention are: the method of this invention realizes the efficient utilization of biomass resources and produces two terminal diols with odd carbon atoms (1,5-pentanediol and 1,3-propanediol). At the same time, the method is simple, green and environmentally friendly, and does not use precious metal catalysts throughout the process.
[0018] This method enables the targeted production of bio-based 1,5-pentanediol and bio-based 1,3-propanediol. This invention uses bio-based dihydropyran and 3-hydroxypropionic acid as raw materials to produce bio-based polymer monomers 1,5-pentanediol and 1,3-propanediol. It features green and clean production, easy operation, and high yield. The use of biomass-based raw materials to produce bio-based chemicals aligns with the dual-carbon development strategy and has broad application prospects. Detailed Implementation
[0019] The present invention will be further illustrated below with specific embodiments. All contents and percentages in this application are by mass.
[0020] Example 1
[0021] Using ZSM-25 (silicon-to-aluminum ratio of 50) purchased from Nankai University as a solid acid catalyst, the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid was carried out in a reactor at a reaction temperature of 100℃. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 5, and N2 was introduced into the system to a pressure of 4 MPa. After 5 hours of reaction, the gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 95%, and the selectivity of tetrahydropyran hydroxypropionate was 80%. Tetrahydropyran hydroxypropionate was obtained by column chromatography.
[0022] Using γ-alumina as a support, a mixed aqueous solution with a metal ion concentration of 0.2M was prepared by mixing copper nitrate, nickel nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 500℃ for 4 hours to obtain the catalyst. The catalyst particles were obtained by tableting and sieving to obtain 20-60 mesh particles. The catalyst composition was 20Cu5Ni0.5Ga / Al2O3 (the numbers before the metals represent the mass percentage of the metal in the catalyst; the meaning is the same in the examples below). 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using 10% H2 / N2 at 600℃ for 1 hour at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃, and high-purity hydrogen was switched to a pressure of 8 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken for analysis using gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 75% for 1,5-pentanediol and 90% for 1,3-propanediol.
[0023] Example 2
[0024] Using ZSM-25 (silicon-to-aluminum ratio of 25) purchased from Nankai University as a solid acid catalyst, the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid was carried out in a reactor at a temperature of 70℃. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 3. N2 was introduced into the system to a pressure of 2 MPa. After 8 hours of reaction, gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 92%, and the selectivity of tetrahydropyran hydroxypropionate was 83%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0025] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, cobalt nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 20Cu2Zn1Ga / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 300℃ for 3 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 180℃ and the pressure was 5MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 40. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 82% for 1,5-pentanediol and 94% for 1,3-propanediol.
[0026] Example 3
[0027] β-hydroxypropionic acid catalyst (silicon-to-aluminum ratio of 25) purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 50°C. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 1. N2 was introduced into the system to a pressure of 1 MPa. After 8 hours of reaction, gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 70%, and the selectivity of tetrahydropyran hydroxypropionate was 83%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0028] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, nickel nitrate, and boric acid in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 25Cu5Ni0.8B / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 400℃ for 3 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 240℃ and the pressure was 8 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 50. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 79% for 1,5-pentanediol and 90% for 1,3-propanediol.
[0029] Example 4
[0030] β-hydroxypropionic acid catalyst (silicon-to-aluminum ratio of 25) purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 70°C. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 1. N2 was introduced into the system to a pressure of 1 MPa. After 6 hours of reaction, gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 90%, and the selectivity of tetrahydropyran hydroxypropionate was 79%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0031] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, zinc nitrate, and lanthanum nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 15Cu1Zn0.5La / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃ and the pressure was 6MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.2 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken for analysis by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 85% for 1,5-pentanediol and 94% for 1,3-propanediol.
[0032] Example 5
[0033] β-(silicon-to-aluminum ratio of 25) solid acid catalyst purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 70℃ and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 0.2, under normal pressure. After 8 hours of reaction, gas chromatography analysis showed that the conversion rate of dihydropyran was 99% and the selectivity of tetrahydropyran hydroxypropionate was 88%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0034] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, zirconium nitrate, and lanthanum nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 20Cu1.5Zr0.5La / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃ and the pressure was 6MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.2 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken for analysis by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 84% for 1,5-pentanediol and 92% for 1,3-propanediol.
[0035] Example 6
[0036] β-hydroxyl propionic acid catalyst (silicon-to-aluminum ratio of 25) purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 100℃ and a molar ratio of 0.5 for dihydropyran to 3-hydroxypropionic acid. The reaction was carried out at atmospheric pressure for 2 hours. Gas chromatography analysis showed a dihydropyran conversion rate of 99% and a selectivity of 80% for tetrahydropyran hydroxypropionic acid ester. Tetrahydropyran hydroxypropionic acid ester was obtained by chromatographic separation.
[0037] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate and lanthanum nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 30Cu3La / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 220℃ and the pressure was 5MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 92% for 1,5-pentanediol and 95% for 1,3-propanediol.
[0038] Example 7
[0039] β-(silicon-to-aluminum ratio of 25) solid acid catalyst purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 100℃ and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 1, under normal pressure. After 2 hours of reaction, gas chromatography analysis showed that the conversion rate of dihydropyran was 83% and the selectivity of tetrahydropyran hydroxypropionate was 85%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0040] Using silica as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, zinc nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 25Cu2Zn1Ga / SiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃ and the pressure was 6MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 50. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 99%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 90% for 1,5-pentanediol and 92% for 1,3-propanediol.
[0041] Example 8
[0042] β-(silicon-to-aluminum ratio of 25) solid acid catalyst purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 50°C and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 0.2, under normal pressure. After 10 hours of reaction, gas chromatography analysis showed that the conversion rate of dihydropyran was 98%, and the selectivity of tetrahydropyran hydroxypropionate was 91%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0043] Using coconut shell activated carbon as a carrier, a mixed aqueous solution with a metal ion concentration of 0.2M was prepared by mixing copper nitrate, zinc nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the carrier, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 25Cu2Zn1Ga / activated carbon. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃ and the pressure was 6MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 50. After 48 hours of reaction, samples were taken for analysis by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 95%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 93% for 1,5-pentanediol and 95% for 1,3-propanediol.
[0044] Example 9
[0045] β-hydroxyl propionic acid catalyst (Si / A ratio of 25) purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 70°C and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 0.2, under normal pressure. After 3 hours of reaction, gas chromatography analysis showed that the conversion rate of dihydropyran was 99% and the selectivity of tetrahydropyran hydroxypropionic acid ester was 90%. Tetrahydropyran hydroxypropionic acid ester was obtained by chromatographic separation.
[0046] Using diatomaceous earth as a carrier, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, zinc nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the carrier, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 25Cu2Zn1Ga / diatomaceous earth. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃ and the pressure was 6MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 50. After 48 hours of reaction, samples were taken for analysis by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 98%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 88% for 1,5-pentanediol and 89% for 1,3-propanediol.
[0047] Example 10
[0048] β-(silicon-to-aluminum ratio of 25) solid acid catalyst purchased from Nankai University was used to carry out the addition esterification reaction of dihydropyran with 3-hydroxypropionic acid in a reactor at 80℃ and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 0.2, under normal pressure. After 3 hours of reaction, gas chromatography analysis showed that the conversion rate of dihydropyran was 99% and the selectivity of tetrahydropyran hydroxypropionate was 87%. Tetrahydropyran hydroxypropionate was obtained by chromatographic separation.
[0049] Using anatase titanium dioxide as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, zinc nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 400℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 25Cu2Zn1Ga / TiO2. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using hydrogen at 200℃ for 2 hours at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 240℃ and the pressure was 6 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 50. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 97%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 85% for 1,5-pentanediol and 87% for 1,3-propanediol.
[0050] Comparative Example 1
[0051] Without using a catalyst, dihydropyran and 3-hydroxypropionic acid were loaded into a reactor and reacted at a temperature of 80°C. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 0.2. 1 MPa of N2 was introduced, and after 3 hours of reaction, the reaction was analyzed by gas chromatography. The conversion rate of dihydropyran was 20%, and the selectivity of tetrahydropyran hydroxypropionic acid ester was 54%.
[0052] Comparative Example 2
[0053] Quartz sand was added to a fixed-bed reactor, and the system temperature was heated to 240°C. The hydrogen pressure was 6 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken and analyzed by gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 3%, and 1,5-pentanediol and 1,3-propanediol were not detected in the product.
[0054] Comparative Example 3
[0055] Using SAPO-34 purchased from Nankai University as a solid acid catalyst, the addition esterification reaction of dihydropyran and 3-hydroxypropionic acid was carried out in a reactor at a reaction temperature of 100℃. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 5. N2 was introduced into the system to a pressure of 4 MPa. After 5 hours of reaction, the gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 35%, and the selectivity of tetrahydropyran hydroxypropionic acid ester was 60%.
[0056] Comparative Example 4
[0057] Using HY (silicon-to-aluminum ratio of 5.4) purchased from Nankai University as a solid acid catalyst, the addition esterification reaction of dihydropyran and 3-hydroxypropionic acid was carried out in a reactor at a reaction temperature of 100℃. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 5. N2 was introduced into the system to a pressure of 4 MPa. After 5 hours of reaction, the gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 33%, and the selectivity of tetrahydropyran hydroxypropionic acid ester was 51%.
[0058] Comparative Example 5
[0059] Using γ-alumina as a support, a mixed aqueous solution with a metal ion concentration of 0.2M was prepared by adding a certain proportion of copper nitrate. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 500℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 20Cu / Al₂O₃. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using 10% H₂ / N₂ at 600℃ for 1 hour at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 200℃, and high-purity hydrogen was switched to a pressure of 8 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken for analysis using gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 61%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 55% for 1,5-pentanediol and 71% for 1,3-propanediol.
[0060] Comparative Example 6
[0061] The β-(silicon-to-aluminum ratio of 25) solid acid catalyst purchased by Nankai University was used to carry out the addition esterification reaction of dihydropyran and 3-hydroxypropionic acid in a reactor at a reaction temperature of 25°C. The molar ratio of dihydropyran to 3-hydroxypropionic acid was 1. N2 was introduced into the system to a pressure of 1 MPa. After 8 hours of reaction, the gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 15% and the selectivity of tetrahydropyran hydroxypropionic acid ester was 77%.
[0062] Comparative Example 7
[0063] Using ZSM-25 (silicon-to-aluminum ratio of 50) purchased from Nankai University as a solid acid catalyst, the addition esterification reaction of dihydropyran and 3-hydroxypropionic acid was carried out in a reactor at a reaction temperature of 40℃ and a molar ratio of dihydropyran to 3-hydroxypropionic acid of 5. N2 was introduced into the system to a pressure of 4 MPa. After 5 hours of reaction, the gas chromatography analysis showed that the conversion rate of 3-hydroxypropionic acid was 25% and the selectivity of tetrahydropyran hydroxypropionic acid ester was 78%.
[0064] Comparative Example 8
[0065] Using γ-alumina as a support, a mixed aqueous solution with a metal ion concentration of 0.2 M was prepared by mixing copper nitrate, nickel nitrate, and gallium nitrate in a certain proportion. This aqueous solution was added to the support, and the mixture was impregnated at room temperature for 12 hours, dried at 100℃ for 12 hours, and calcined at 500℃ for 4 hours to obtain the catalyst. The catalyst was then pressed into tablets and sieved to obtain 20-60 mesh particles. The catalyst composition was 20Cu5Ni0.5Ga / Al2O3. 2 ml of the catalyst was loaded into a fixed-bed reactor and activated using 10% H2 / N2 at 600℃ for 1 hour at a gas hourly space velocity (GHSV) of 1000 h⁻¹. After activation, the temperature was lowered to 150℃, and high-purity hydrogen was switched to a pressure of 8 MPa. A dioxane solution of tetrahydropyran hydroxypropionate was used as the raw material, with a tetrahydropyran hydroxypropionate concentration of 10%. The liquid hourly space velocity of the liquid raw material was 0.5 h⁻¹, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate was 60. After 48 hours of reaction, samples were taken for analysis using gas chromatography. The conversion rate of tetrahydropyran hydroxypropionate was 11%. The selectivity calculation was based on theoretical selectivity, with a selectivity of 66% for 1,5-pentanediol and 70% for 1,3-propanediol.
[0066] As shown in Comparative Examples 1-2, the reactivity between dihydropyran and 3-hydroxypropionic acid is very low in the absence of a catalyst, and tetrahydropyran hydroxypropionate does not produce a diol product in the absence of a metal hydrogenation catalyst. Comparative Examples 3-4 and Examples 1-10 show that the type of molecular sieve used has a significant impact on the reaction performance of dihydropyran and hydroxypropionic acid. Comparative Example 5 shows that the single-metal copper catalyst has the ability to catalyze the hydrogenation of tetrahydropyran hydroxypropionate, but both its activity and product selectivity are low. Examples 1-10 demonstrate that dihydropyran and 3-hydroxypropionic acid can undergo an efficient addition-esterification reaction in the presence of a solid acid catalyst to produce a product rich in tetrahydropyran hydroxypropionate. The tetrahydropyran hydroxypropionate feedstock can undergo an efficient hydrogenation reaction in the presence of a hydrogenation catalyst, producing 1,5-pentanediol and 1,3-propanediol with high activity and high selectivity. It is evident that the method of this invention enables the co-production of bio-based 1,5-pentanediol and 1,3-propanediol from bio-based raw materials dihydropyran and 3-hydroxypropionic acid through a two-step process of addition esterification and subsequent hydrogenation, achieving the simultaneous production of two key odd-numbered carbon terminal diols.
Claims
1. A method for producing bio-based 1,5-pentanediol and 1,3-propanediol from dihydropyran and hydroxypropionic acid, characterized in that: The method includes the following steps: (a) In the presence of a solid acid catalyst, dihydropyran undergoes an addition esterification reaction with 3-hydroxypropionic acid, and after separation, tetrahydropyran hydroxypropionic acid ester is obtained; the solid acid catalyst is one or both of ZSM-25 molecular sieve and β molecular sieve. (b) In the presence of a hydrogenation metal catalyst and under a hydrogen atmosphere, tetrahydropyran hydroxypropionate undergoes a hydrogenation reaction to produce the target products 1,5-pentanediol and 1,3-propanediol. The hydrogenation metal catalyst comprises three parts: a metal active component, an additive, and a support. The metal active component is the metal element Cu, or one or two of Cu and Ni, Co. The additive is selected from one or more of the additive elements Zn, B, Zr, Ga, and La. The support is an inorganic porous material selected from one or more combinations of SiO2, Al2O3, TiO2, silicon-aluminum mixed oxide, titanium-silicon mixed oxide, diatomaceous earth, kaolin, and activated carbon. The active metal component in the hydrogenation metal catalyst accounts for 2-50% of the catalyst weight by mass, and the promoter accounts for 0.01-8% of the catalyst weight by mass. The addition esterification reaction conditions in step (a) are: reaction temperature 50~200℃, reaction pressure 0.1~10MPa. The conditions for the hydrogenation reaction in step (b) are: reaction temperature 170~300℃ and reaction pressure 0.1~15MPa.
2. The method according to claim 1, characterized in that, The addition esterification reaction conditions in step (a) are: reaction temperature 50~170℃, reaction pressure 0.1~8MPa, and molar ratio of dihydropyran to 3-hydroxypropionic acid 20:1~1:
20.
3. The method according to claim 2, characterized in that, The addition esterification reaction conditions in step (a) are: reaction temperature 50~150℃, reaction pressure 0.1~6MPa, and molar ratio of dihydropyran to 3-hydroxypropionic acid 15:1~1:
15.
4. The method according to claim 2, characterized in that, The addition esterification reaction conditions in step (a) are: reaction temperature 50~100℃, reaction pressure 0.1~4MPa, and molar ratio of dihydropyran to 3-hydroxypropionic acid 10:1~1:
10.
5. The method according to claim 2, characterized in that, The molar ratio of dihydropyran to 3-hydroxypropionic acid is 5:1 to 1:
5.
6. The method according to claim 1, characterized in that, The conditions for the hydrogenation reaction in step (b) are: reaction temperature 170~280℃, reaction pressure 1~12MPa, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate 5:1~100:
1.
7. The method according to claim 6, characterized in that, The conditions for the hydrogenation reaction in step (b) are: reaction temperature 170~260℃, reaction pressure 3~9MPa, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate 10:1~90:
1.
8. The method according to claim 6, characterized in that, The conditions for the hydrogenation reaction in step (b) are: reaction temperature 170~240℃, reaction pressure 5~8MPa, and the molar ratio of hydrogen to tetrahydropyran hydroxypropionate 20:1~70:
1.
9. The method according to claim 6, characterized in that, In step (b), the molar ratio of hydrogen to tetrahydropyran hydroxypropionate is 40:1 to 60:
1.
10. The method according to claim 1, characterized in that, The reactors used for the reactions in steps (a) and (b) are selected from one of the following: fixed bed, slurry bed, fluidized bed, and high-pressure reactor.
11. The method according to claim 1, characterized in that, The active metal component in the hydrogenation metal catalyst accounts for 5-40% of the catalyst weight by mass, and the promoter accounts for 0.05-6% of the catalyst weight by mass.
12. The method according to claim 1, characterized in that, The active metal component in the hydrogenation metal catalyst accounts for 10-35% of the catalyst weight by mass, and the promoter accounts for 0.1-5% of the catalyst weight by mass.
13. The method according to claim 1, characterized in that, The active metal component in the hydrogenation metal catalyst accounts for 15-30% of the catalyst weight by mass; the promoter accounts for 0.5-3% of the catalyst weight by mass.
14. The method according to claim 1 or 11, characterized in that, The hydrogenation metal catalyst in step (b) is prepared by at least one of the following methods: impregnation, precipitation, and physical grinding. Wherein: the impregnation method involves adding a certain amount of metal salt mixture solution to a carrier, and obtaining a catalyst after drying and calcination processes; The precipitation method uses a metal salt mixture solution as a metal precursor and one or more of urea, ammonia, sodium carbonate, and sodium hydroxide as a precipitant. The metal precursor is added to the precipitant solution, or the precipitant solution is added to the metal precursor, or the metal precursor and precipitant are added simultaneously to a precipitation vessel containing a solvent. After aging, the mixture is filtered, washed, dried, and calcined to obtain a catalyst. An inorganic porous material carrier is added to the precipitation system during the precipitation process. The physical grinding method involves mechanically mixing an inorganic porous carrier and a metal salt directly in a mortar or ball mill, followed by drying and calcination to obtain the catalyst.
15. The method according to claim 14, characterized in that, The drying temperature is 60~150℃, and the calcination temperature is 250~800℃; The precipitation temperature is 25~90℃; the aging temperature is 25~90℃.
16. The method according to claim 1, characterized in that, The hydrogenation metal catalyst described in step (b) needs to be activated before use. The activation is carried out in a hydrogen-containing atmosphere with a hydrogen content of 0.05% to 100%, and the remaining gases are nitrogen and / or argon. The activation conditions are: temperature 100 to 800°C, time 0.5 to 72 h, and gas space velocity 10 to 10000 h⁻¹. -1 .
Citation Information
Patent Citations
Catalyst for preparing pentanediol from biomass, and preparation method and application thereof
CN108620122A
Production of 1,5-pentanediol via upgrading of tetrahydrofurfuryl alcohol
US10077224B1
